2018
DOI: 10.18632/oncotarget.26182
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal survivin facilitates vesicle internalization

Abstract: Survivin, a member of the inhibitor of apoptosis (IAP) protein family plays a significant role in cell fate and function. It is significantly overexpressed in tumor cells and has been identified in most cancer cell types. A novel extracellular population has recently been identified and its function is still unknown. Emerging evidence continues to shed light on the important role the tumor microenvironment (TME) has on tumor survival and progression. This new population of survivin has been seen to enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…Gonda et al reported that survivin in cancer EVs facilitated vesicle internalization. EV internalization was reduced when survivin was inhibited [43]. Eitan et al found that plasma EVs from aging individuals were more easily internalized by B cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…Gonda et al reported that survivin in cancer EVs facilitated vesicle internalization. EV internalization was reduced when survivin was inhibited [43]. Eitan et al found that plasma EVs from aging individuals were more easily internalized by B cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the tumor microenvironment, survivin expression in exosomes appears to support cell proliferation and treatment resistance (17,19,20). Abs to survivin can reduce the ability of exosomes to internalize on the target cell (20). In our model, the localization of survivin to the external cell surface would allow for recognition by an Ab and could inhibit the role of survivin in supporting persistence of autoreactive cells.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we demonstrated expression of survivin on the outer surface of CD20 + cells, suggesting that survivin may have a role in cell-cell signaling. In the tumor microenvironment, survivin expression in exosomes appears to support cell proliferation and treatment resistance (17,19,20). Abs to survivin can reduce the ability of exosomes to internalize on the target cell (20).…”
Section: Discussionmentioning
confidence: 99%
“…Two proteins commonly active in caveolae-dependent endocytosis, which have also been identified on the surface of exosomes, are the insulin receptor and albumin [34,38,39]. The cellular insulin receptor itself has also recently been found to influence exosome uptake [18].…”
Section: Caveolin-dependent Endocytosismentioning
confidence: 99%
“…The methods by which exosomes influence the cells with which they interact are still under review. Some exosomes have been shown to fuse to the recipient cell [15,16], while others are internalized by specific receptor-ligand interactions [17,18] or by stimulating an indirect uptake by macropinocytosis [19]. Exosome binding to cells has been seen both as a mechanism of transferring luminal contents [15,16] and as an initial step in the endocytosis process [17,20].…”
Section: Introductionmentioning
confidence: 99%